TAX PLANNING IN BRAZIL AFTER THE 2023 TAX REFORM: THE CASE OF A COMPANY FROM PIRACICABA, SP - Stenico, Jéssica Helena da Costa; Nascimento, Julio Cesar (Seven Editora, 2026)
This study analyzed the impacts of the 2023 tax reform on the tax planning of a metallurgical company located in Piracicaba-SP, considering the structural changes promoted by Constitutional Amendment No. 132/2023. The general objective was to identify how the replacement of consumption taxes with CBS, IBS, and Selective Tax influenced fiscal management, operational costs, and the organization's competitiveness. To this end, a bibliographic, descriptive, and explanatory methodology was applied, based on legislation, specialized literature, and semi-structured interviews conducted with professionals from the analyzed company. The research revealed that the reform brought opportunities for tax simplification and greater predictability, but also generated uncertainties regarding technological adaptation, the extinction of tax benefits, and the need to review the logistics chain. The data showed that the company began adjustments to its ERP systems and sought support from consultancies, but still faced challenges related to regulatory uncertainty and adaptation costs. It was found that the absence of structured internal planning limited the efficiency of adaptation strategies, requiring additional measures to mitigate tax risks. It was concluded that tax planning assumed a strategic role in the new context and that the adoption of actions such as internal committees, technical training, and logistical review proved fundamental to ensuring the company's competitiveness and legal compliance.